(untitled) (Communication & Society, 2023)
This study examines the contemporary condition of Indonesian local game developers as a part of the national creative workers. The case study method is applied in parallel with the participant’s observation and the results were retrieved by exploring and comparing interviews and observation findings. The subjects of this study include state-related ministries (The Ministry of Manpower and The Ministry of Tourism and Creative Economy), 12 founders of the Indonesian first-generation local game developer studios, 10 experienced local game workers, and two representatives of the Indonesian Game Association as a labor union. The results figured out the characteristics of Indonesian local game developers as youth-subcultural movements and recent challenges of state patronage, incentives, and human resource issues. The situation forced them to survive and organize a supportive labor union as a major incubator platform and crowdfunding scheme in developing local games.